HUBUNGAN REMUNERASI DENGAN KINERJA DAN KEPUASAN KERJA STAF MEDIS DI RSUP DR. M. DJAMIL PADANG - oea oea (HUMAN CARE JOURNAL, 2021)
The changes in the pattern of providing medical services from the fee for service to the remuneration system cause problems among medical staff, so that it can have an adverse effect on the performance and job satisfaction of staff at Dr. M. Djamil Hospital, Padang. This study aims to determine whether there is a relationship between remuneration and the performance and satisfaction of medical staff at M. Djamil Hospital, Padang. The research method is descriptive analytic with quantitative and qualitative approaches (mix method). Systematic random sampling technique was obtained by 72 medical staff and 8 informants in qualitative research taken by purposive sampling. The results of the analysis using statistical tests found a significant relationship between remuneration and performance (p = 0.012 or <0.05) and there was no significant relationship between remuneration and job satisfaction (p = 0.881 or> 0.05). Based on qualitative analysis, it was concluded that most medical staff lacked understanding of remuneration, the implementation was not transparent and there was no clarity between IKI and remuneration, remuneration had an effect on improving performance and was related to staff satisfaction. We need to improve understanding of remuneration and information among staff in evaluating staff performance